PENGARUH PENERAPAN METODE AKTIF TIPE GUIDED NOTE TAKING TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMPN 3 SOLOK SELATAN TAHUN PELAJARAN 2012/2013 - Condra, Talbi; Armen, Armen; Maizeli, Annika (STKIP PGRI Sumbar, 2013)
ABSTRACTThe low student learning outcomes due to the lack of biological activity of students , lack of facilities and infrastructure in schools and students in understanding the difficulty of the material being studied . One way to improve student learning outcomes by applying active methods type Guided Note Taking . This study aimed to determine the effect of the application of active methods type Guided Note Taking on learning outcomes biology class VII SMPN 3 South Solok the academic year 2012/2013.This type of research is experimental research . The population in this study were students of class VII SMPN 3 South Solok the academic year 2012/2013 which consists of 4 classes . Sampling was purposive sampling techniques , in order to obtain samples of the class 2 class VII.B as the experimental class and the control class VII.D class . From the results of experimental studies it appears that the class average value of 73.13 while the control class had an average score of 56.48 .the result of hypothesis test obtained ttable the level of confidence 95%= (Î±=0,05) is 1,67 and tacount =7,43 it meant tacount>ttable therefore, the hypothesis in thisÂ search is received . It can be concluded that the type of active learning methods Guided Note Taking biology to improve learning outcomes of students of class VII SMPN 3 South Solok the academic year 2012/2013 .Â Â